Nuclear accident emergency desktop deduction and decision-making system and method - FANG SICONG; LIU JIANGE; DAI HAO; LUO YING (2025)
The invention belongs to the field of nuclear accident emergency, and particularly relates to a nuclear accident emergency desktop deduction and decision-making system and method.The method comprises the steps that a system management module manages system data, sends source item information and environment information to a simulation prediction module, obtains accident process data and protection evaluation data and stores the accident process data and the protection evaluation data; the project information and the user information are sent to the deduction guiding module, and rescue cases, accident cases and decision data are obtained and stored; the deduction guidance module implements deduction action simulation and guidance intervention control; the simulation and prediction module performs accident and action calculation and simulation and prediction; the deduction guidance module sends guidance intervention data and accident intervention data to the simulation prediction module, and obtains an accident